2021
DOI: 10.4314/jasem.v25i7.32
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Ganoderma lucidum (Curtis) P. Karst. From the Wild in Lagos through Tissue Culture Techniques and Cultivation on Sawdust of Six Nigerian Hardwoods

Abstract: Cultivation of Ganoderma lucidum (Curtis) P. Karst, a medicinal mushroom known for antioxidant, antitumor, anti-inflammatory, and immunomodulatory activities is not practiced in Nigeria. Tree species used for cultivation in Asia, America and Europe are not available in Nigeria. The present study investigated indigenous hardwoods and their supplementation with rice and wheat bran as substrates for its cultivation. Six hardwoods (Mansonia altissima (A Chev.) A Chev., Avecennia germinans (L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Diverse substrate formulations have been reported and employed for the large-scale production of this mushroom to meet its demand. In Lagos Nigeria, Adongbede and Atoyebi, (2021) cultivated G. lucidum (Curtis) P. Karst. on the sawdust (substrate) of six indigenous hardwoods supplemented with rice and wheat bran.…”
Section: Ganoderma Lucidum Distribution and Cultivationmentioning
confidence: 99%
“…Diverse substrate formulations have been reported and employed for the large-scale production of this mushroom to meet its demand. In Lagos Nigeria, Adongbede and Atoyebi, (2021) cultivated G. lucidum (Curtis) P. Karst. on the sawdust (substrate) of six indigenous hardwoods supplemented with rice and wheat bran.…”
Section: Ganoderma Lucidum Distribution and Cultivationmentioning
confidence: 99%
“…During the process of cultivating reishi mushrooms, several researchers have added numerous additives (such as wheat and corn and rice bran, soybean meal, cottonseed meal, malt, sugarcane bagasse, sunflower meal or molasses) to corncobs and straw (Veena and Pandey, 2011;Rashad et al, 2019;Yuliana et al, 2020), sawdust of oak, mango, acacia, tuni, paddy straw, wheat straw, and soybean waste (Jandaik et al, 2013), sawdusts of sheesham, mango, and poplar (Mehta et al, 2014), sunflower seed husks (Gonzalez-Matute et al, 2002), paddy husk and plant waste (Yang et al, 2003;Rashad et al, 2019;Yuliana et al, 2020), tea waste (Peksen and Yakupoğlu, 2009), sawdust of various trees (Erkel, 2009;Nguyen et al, 2019;Atila, 2020;Adongbede and Atoyebi, 2021), olive plant residues (Koutrotsios et al, 2019), broad bean stalks, cotton stalks and wheat straw (Rashad et al, 2019;Atila, 2020), soybean straw and bean straw (Atila, 2020), hazelnut shells (Puliga et al, 2022) and found differences among the substrates. Growers generally prefer to use the best and cheapest substrate materials available locally (Özçelik and Pekşen, 2007).…”
Section: Introductionmentioning
confidence: 99%